2017
DOI: 10.25115/ejrep.v6i14.1262
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regression analysis of epistemological beliefs, learning approaches, and self-regulated learning

Abstract: Introduction. Recent research in educational psychology has explored student approaches to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 69 publications
2
22
0
3
Order By: Relevance
“…Other prior studies have shown similar relationships between learning approaches and self-regulation (Phan, 2008) and between the teachinglearning process and self-regulation (De la Fuente, Justicia, & Berben, 2005). Phan (2008) performed a regression analysis and concluded that deep motivation predicted self-regulated learning in 603 university students in the South Pacific. Similarly, De la Fuente et al (2005) showed that self-regulation has a positive correlation with the deep approach and a negative correlation with the surface approach in 492 university students in Almería and Granada (Spain).…”
Section: Discussionmentioning
confidence: 71%
“…Other prior studies have shown similar relationships between learning approaches and self-regulation (Phan, 2008) and between the teachinglearning process and self-regulation (De la Fuente, Justicia, & Berben, 2005). Phan (2008) performed a regression analysis and concluded that deep motivation predicted self-regulated learning in 603 university students in the South Pacific. Similarly, De la Fuente et al (2005) showed that self-regulation has a positive correlation with the deep approach and a negative correlation with the surface approach in 492 university students in Almería and Granada (Spain).…”
Section: Discussionmentioning
confidence: 71%
“…The evidence to date reveals the value of personal self-regulation in accounting for how stress is dealt with while learning (De la Fuente & CardelleElawar, 2011), and in predicting self-regulated learning (Phan, 2006(Phan, , 2008 and performance . The cumulative evidence appears to present us with an essential, personal macro-construct, having a meta-motivational and meta-affective nature (Bandura, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence in the context of the Pacific region, at present, suggests there is credence to further research investigation into the relations between epistemological beliefs and approaches to learning. Extant research studies by Mugler, Phan, and their colleagues (Mugler & Landbeck, 1997;Phan & Deo, 2007, In press;Richardson et al, 1995) in learning approaches, and the work of Phan (2006Phan ( , 2008aPhan ( , 2008b in personal epistemology have advocated the importance of one's sociohistorical milieu. The theoretical contention, arising from a number of reasons, underlies the belief that personal epistemology and learning approaches are deeply embedded in the sociocultural and family environments of individuals.…”
Section: The Present Study: a Qualitative Approachmentioning
confidence: 99%
“…First, the issue pertaining to the social and cultural origins of epistemological beliefs has been raised by a number of researchers. The work of Mugler, Richardson, Phan and their colleagues (Mugler & Landbeck, 1997;Phan, 2008aPhan, , 2008b involving Pacific Islands and Indo-Fijian students has placed an important emphasis on the social environment and one's socio-historical background. This theoretical contention warrants the need to situate students' epistemological beliefs and their learning approaches in a sociocultural framework.…”
Section: Introductionmentioning
confidence: 99%